2011
DOI: 10.1007/s00540-011-1170-z
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative carbohydrate-rich beverage reduces hypothermia during general anesthesia in rats

Abstract: Preoperative carbohydrate loading reduces hypothermia in rats under general anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In body temperature assessments, we were not able to achieve any positive results, but showed the propensity to maintain temperatures in the per-protocol analyses. Preoperative CHO loading has been shown to attenuate the development of hypothermia during general anaesthesia in rats [ 19 ]. However, in this study, no surgical procedures had been performed, which may not accurately reflect a clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In body temperature assessments, we were not able to achieve any positive results, but showed the propensity to maintain temperatures in the per-protocol analyses. Preoperative CHO loading has been shown to attenuate the development of hypothermia during general anaesthesia in rats [ 19 ]. However, in this study, no surgical procedures had been performed, which may not accurately reflect a clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, special and expensive equipment such as surgical instruments, microscopes or mechanical ventilators for small laboratory mammals can be necessary. Hypothermia, while not exclusive to small mammals, is a special concern in these animals and an important cause of unintended death under anesthesia [ 8 10 ]. High metabolic rates and difficulties monitoring of respiratory [ 11 ] and cardiovascular function reliably [ 11 , 12 ] contribute to the complexity of the anesthetic management.…”
Section: Introductionmentioning
confidence: 99%
“…The main ingredients of the carbohydrate beverages used in this study were maltodextrin, fructose, glucose, and taurine (amino acids), all of which are effective nutrients for body temperature maintenance. Yatabe et al 8 demonstrated in an animal experiment that preoperative oral carbohydrate loading reduced hypothermia in rats during general anesthesia; however, this result was not confirmed in clinical studies. Ozer et al 12 conducted a randomized controlled trial of female patients during general anesthesia for the removal of hysteromyoma.…”
Section: Discussionmentioning
confidence: 93%
“…[5][6][7] An animal study found that carbohydrate loading can maintain the body temperature of rats during general anesthesia. 8 Nutrient-induced thermogenesis to increase a patient's body temperature has been proven to be effective for preventing intraoperative hypothermia. Continuous intravenous (IV) infusion of amino acids 9,10 or fructose 11 before surgery can effectively prevent decreases in a patient's core temperature during anesthesia.…”
Section: Glossarymentioning
confidence: 99%